Framing as modus operandi for social movements: The case of Black Lives Matter - Sádaba, Teresa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
From a symbolic and cultural approach to the social movements, framing theory has contributed to explain meanings and strategies for mobilization. Also, the theory has evolved in the media research, and media frames have to be also considered in the collective action. This paper clarifies how frames work in this context and describes their ability to give legitimization and congruence to the movement. The case of Black Lives Matter is an example of the use of framing and its consequences for the movement.
Keywords: framing; media frames; collective action; Black Lives Matter